The development and characterization of a stable Coxsackievirus A16 infectious clone with Nanoluc reporter gene - Yu, Rui; Wang, Min; Liu, Lizhen; Yan, Jingjing; Fan, Jun; Li, Xiaohong; Kang, Miaomiao; Xu, Jianqing; Zhang, Xiaoyan; Zhang, Shuye (Frontiers in Microbiology, 2023)
Coxsackievirus A16 (CA16) belongs to the Human Enterovirus A species, which is a common pathogen causing hand, foot, and mouth disease in children. Currently, specific vaccines and drugs against CA16 are unavailable, and there is an unmet need to further understand the virus and invent effective treatment. Constructing a CA16 infectious clone with a reporter gene will greatly facilitate its virological studies. Here, we first reported the construction of a CA16 infectious clone (rCA16) whose progeny is highly replicative and virulent in suckling mice. On the basis of rCA16, we further inserted a NanoLuc (Nluc) reporter gene and made the rCA16-Nluc clone. We found that the Nluc gene in rCA16-Nluc is stable during continuous growing in Vero cells and thus allowed detection of a steady luciferase signal in rCA16-Nluc-infected Vero cells over ten passages. Its application in antivirals characterization and high-throughput screening is exemplified by measuring IC50, CC50, and selection index of guanidine hydrochloride, ribavirin, chloroquine, and ammonium chloride against CA16. Finally, we showed that rCA16-Nluc based assay greatly simplified the CA16 neutralizing antibody tests. Thus, these two CA16 infectious clones will be robust tools for future enterovirus studies and antivirals development.